Pemberian MP- ASI dengan Kejadian Stunting Pada Balita di Puskesmas Rejosari Pekanbaru - Isnaniar; Norlita, Wiwik; Hasanah, Neng (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2024)
Data from 2020 shows that the highest number of stunted toddlers in the world comes from Asia (53%) followed by Africa (41%). The largest proportion comes from South Asia, namely 30.7%, then in second place is Southeast Asia at 27.4%, while the lowest proportion is in East Asia, namely 4.9%. In Southeastern Asia Regional in 2005-2007, the first position was occupied by Timor Leste with a prevalence of 48.8%, then in second position was Indonesia with 31.8% (WHO, 2021). The factors that cause stunting are mainly influenced by nutritional intake, which has a significant influence on growth. Failure to implement early breastfeeding initiation (IMD), failure to provide exclusive breast milk (ASI), and early weaning can be factors in stunting. Things that need to be considered when providing complementary breast milk (MP-ASI) are the quantity, quality and safety of the food provided (Ministry of Health of the Republic of Indonesia, 2018). More than 40% of babies are introduced to complementary foods too early (before reaching six months), the food consumed by 40% of children aged 6–24 months is not as varied as it should be, and 28% of children do not get food with sufficient frequency. (UNICEF, 2020). The purpose of this study was to determine the Effect of Providing Complementary Breastfeeding with the Incidence of Stunting in Toddlers at the Rejosari Health Center, Pekanbaru. (2012). The research design used was Correlational study, the Population in this study were all toddlers who were treated at the Rejosari Health Center, Pekanbaru with a sample size of 47 respondents. The results of the study showed that toddlers who did not receive exclusive breastfeeding were 9 respondents and were at risk of stunting (-3 to <2 SD Stunting), and 23 respondents were given inappropriate complementary feeding so that it can be concluded that providing complementary feeding has an effect on the incidence of stunting.